The encyclopedia of Ireland - Lalor, Brian, 1941- (New Haven : Yale University Press, 2003)
Publisher's description: The Encyclopedia of Ireland is the most comprehensive book to date on all aspects of Irish life, culture, and history. It encompasses the whole of Ireland--its islands and seas, its people both home and abroad--and provides fascinating facts about subjects from prehistory to the present.
Includes bibliographical references and indexes.
Koleksi sumbangan Tun (Dr.) Ahmad Sarji Abdul Hamid.
Keywords: Ireland -- Encyclopedias; Northern Ireland -- Encyclopedias